[Letter] 1851 Feb. 7 [to] R.W. Pohlman Esq. - La Trobe, Charles Joseph, 1801-1875.; Pohlman, Robert William, 1811-1877. (1851)
Letter offers R.W. Pohlman the position of trustee of Melbourne General Cemetery.
Manuscript reference no.: NLA MS 551.
Keywords: Melbourne General Cemetery